2017
DOI: 10.1017/s0960258517000034
|View full text |Cite
|
Sign up to set email alerts
|

Habitat-correlated seed germination and morphology in populations of Phillyrea angustifolia L. (Oleaceae)

Abstract: The broad aim of this work was to study intraspecific variation of seed germination in Phillyrea angustifolia L. (Oleaceae), a species with a hard (water-permeable) endocarp. Germination of seeds from six different wild populations was correlated with traits related either to seed morphology or to environmental parameters. Germination of naked seeds (seeds without endocarp) at the optimum germination conditions was similar among populations and individuals, but great differences could be detected regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Such results could be related to the effects of ion toxicity on seed germination (Panuccio et al, 2014). The different responses of plants to salinity are likely caused by the genetic traits of these species (Vu et al, 2015;Chamorro et al, 2017) and their growing conditions (Mira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Such results could be related to the effects of ion toxicity on seed germination (Panuccio et al, 2014). The different responses of plants to salinity are likely caused by the genetic traits of these species (Vu et al, 2015;Chamorro et al, 2017) and their growing conditions (Mira et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Seed heterogeneity may be associated with ecological strategies that have evolutionary significance. Morphological heterogeneity within a population may occur in seed size, shape or colour (Baskin and Baskin, 1998; Imbert, 2002; Matilla et al , 2005; Zaidi et al , 2010), and has been related to physiological properties, including dormancy (Duran and Retamal, 1989; Rodríguez et al , 2015), germination (Puga-Hermida et al , 2003; Mira et al , 2011b; 2017), and longevity (Kochanek et al , 2009; Niedzielski et al , 2009; Nagel and Borner, 2010). Seed characteristics may also vary within plant and even fruit (Venable, 1985; Guzzon et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, germination is highly responsive to the immediate environment of the seeds (e.g., Grime et al, 1981;Khan and Gulzar, 2003;Shahriari et al, 2014;Finch et al, 2019) as well as to the environment of their origin (e.g., Roach and Wulff, 1987;Cendán et al, 2013;Walter et al, 2016;Finch et al, 2019). Recent studies found considerable intraspecific variation in germination percentage, with populations from the warmest conditions showing the highest germination in all study treatments (Santo et al, 2015) or at least one study treatment (e.g., Ndihokubwayo et al, 2016;Bauk et al, 2017;Mira et al, 2017). Cavieres and Arroyo (2000) and Spindelbock et al (2013) found higher temperature requirements for germination in populations coming from colder, alpine conditions, which was explained as cold avoidance.…”
mentioning
confidence: 99%